2021
DOI: 10.1016/j.clae.2020.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Ocular health of children wearing daily disposable contact lenses over a 6-year period

Abstract: To report on the ocular health and safety of children fit with soft hydrogel daily-disposable contact lenses, and followed for 6-years in a double-masked clinical trial investigating the performance of a dual-focus contact lens designed to control myopia progression. Methods: Children aged 8− 12 years, naïve to contact lens wear, were enrolled across four international sites. During years 1-3, children were randomised to either MiSight® 1 day or Proclear® 1 day (both omafilcon A, CooperVision, Inc.). The lense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Bullimore 13 reported a corneal infiltrative event rate of 136 cases per 10,000 years of wear (95% CI, 50 to 300), based on aggregation of data from 3 prospective studies of children wearing soft contact lenses between the ages of 8 and 14 years. The 6-year MiSight follow-up study found a corneal infiltrative event rate of 61 cases per 10,000 patient-years (95% CI, 24 to 157) 8 . Our study found an incidence rate of 197 cases per 10,000 patient-years of wear (95% CI, 118 to 308).…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Bullimore 13 reported a corneal infiltrative event rate of 136 cases per 10,000 years of wear (95% CI, 50 to 300), based on aggregation of data from 3 prospective studies of children wearing soft contact lenses between the ages of 8 and 14 years. The 6-year MiSight follow-up study found a corneal infiltrative event rate of 61 cases per 10,000 patient-years (95% CI, 24 to 157) 8 . Our study found an incidence rate of 197 cases per 10,000 patient-years of wear (95% CI, 118 to 308).…”
Section: Discussionsupporting
confidence: 45%
“…A total of 2713 patient-years of wear elicited an annualized rate of noninfectious inflammatory adverse events of 660 cases per 10,000 years of wear (95% confidence interval [CI], 390 to 1050), and two cases of presumed or probable microbial keratitis resulted in a rate of 7.4 cases per 10,000 years of wear 6 . A subset of 144 of those children who were 8 to 12 years old at baseline and were prospectively examined for 6 years exhibited a corneal infiltrative event rate of 61 cases per 10,000 patient-years of wear, with no serious adverse events reported 8 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the incidence of corneal infiltrative events and microbial keratitis in children 12 years and younger-in whom myopia control is likely to be initiated-is no higher than that observed in adults and may be lower. 85,86 The peak complication rate at 18-25 years suggests that behavioral and lifestyle factors may have a significant influence. 87 For 8-12-year-olds, parents are more likely to be involved in lens care.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…So due to these clinical scenarios, daily disposable contact lenses could be the best wearing options for contact lens users during pandemic of COVID-19. 11,13…”
Section: Why To Use Contact Lenses Even During Covid-19?mentioning
confidence: 99%